Discovery Learning Learning Model to Improve Thinking Creativity and Problem Solving - Wahyu, Suhartati; Neviyarni, Neviyarni; Nirwana, Herman (Consilium, 2021)
As a teacher, it is important to be able to choose the right learning model for students. This means taking into account their current state or condition, the materials and resources available to them, and the learning style that will work best. It is also important to be aware of which learning model is most appropriate for the specific topic or content being studied. One learning model that is considered to improve creative thinking andproblem-solvingskills is discovery learning. The purpose of this literature review is to describe how a discovery learning model can improve students' creative thinking skills and problem-solving. The research method used is a literature review approach, which is to review existing journals or research articles. The result of this literature review is the contribution of the discovery learning model in improving students' creative thinking skills and problem-solving